(untitled) (Jurnal Kesehatan STIKes IMC Bintaro, 2025)
Introduction: Nutrition problems occur in every life cycle, starting from the womb (fetus), infants, children, adults and old age. The first three years of life are a critical period, because during this period there is rapid growth and development. Nutritional disorders that occur in this period are permanent, irreversible even if the nutritional needs of the next period are met. Research Objective To provide information to all parents and the general public about the importance of fulfilling nutritional needs in children aged 1-3 years at the posyandu in Cilalung village. Methods: The type of research used is quantitative, the design used is correlational analytic type with a cross sectional approach. The population used was parents with children aged 1-3 years at the posyandu in Cilalung village. The instrument used was a questionnaire sheet and an inform consent sheet given to parents. Analysis with Chi-Square Test (fisher exact test). Research Results: In this study, the highest age of respondents was 4 years old (31.9%), most of them were female 29 (61.7%), when before being given storytelling therapy who experienced anxiety levels the majority were more anxious 26 (55.3%), and after being given storytelling therapy the largest proportion occurred in children who did not experience anxiety 27 (57.4%). Conclusion: There is a relationship and no relationship in this study can be seen from the bivariate results. 0.337 - 0.623) which means the P value (> 0.05) and the Ho hypothesis is accepted. Suggestion: So that this research can be a learning material for all readers, especially for parents and health workers, so that they can provide balanced nutritional intake for children under five so that growth is not disturbed.